Insulating slurry and its manufacturing method, positive electrode plate, secondary battery, battery module, battery pack, and power consumption device

JP7651675B2Active Publication Date: 2025-03-26CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023501548
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-03-26
Estimated Expiration
2041-12-29

Smart Images

  • Figure 0007651675000009
    Figure 0007651675000009
  • Figure 0007651675000010
    Figure 0007651675000010
  • Figure 0007651675000011
    Figure 0007651675000011
Patent Text Reader

Abstract

The present application provides an insulating slurry and a manufacturing method thereof, a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consumption device, the insulating slurry comprising a resin, an inorganic filler, and an organic solvent, the resin being selected from a polyfluorinated olefin resin produced by a suspension polymerization method, and the inorganic filler being selected from a two-dimensional inorganic material, the present application can simultaneously improve the coating speed of the insulating slurry and the safety performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of battery technology, and in particular to an insulating slurry and a manufacturing method thereof, a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consuming device. [Background technology]

[0002] In recent years, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as electric tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. With the application and popularity of secondary batteries, their safety issues have been attracting more and more attention, and if the safety issues of secondary batteries cannot be guaranteed, the secondary batteries cannot be used. Therefore, how to improve the safety performance of secondary batteries is currently a technical problem that needs to be solved quickly. Summary of the Invention

[0003] The present application aims to provide an insulating slurry and a manufacturing method thereof for simultaneously improving the coating speed of the insulating slurry and the safety performance of a secondary battery, as well as a positive electrode plate, a secondary battery, a battery module, a battery pack, and a power consumption device.

[0004] According to a first aspect of the present application, there is provided an insulating slurry comprising a resin, an inorganic filler and an organic solvent, the resin being selected from a polyfluorinated olefin resin produced by a suspension polymerization method, and the inorganic filler being selected from a two-dimensional inorganic material.

[0005] In the technical solution of the insulating slurry of the present application, the polyfluorinated olefin resin produced by the suspension polymerization method is used in combination with a two-dimensional inorganic material to suppress the migration of the insulating slurry to the positive electrode slurry coating area, and the width of the blurred area of ​​the fusion area can be significantly reduced while improving the coating speed, thereby improving the safety performance of the secondary battery. The technical solution of the insulating slurry of the present application can also ensure that the secondary battery has a high energy density. The insulating coating produced by the insulating slurry of the present application can simultaneously have high mechanical strength, high heat resistance, high insulation, high adhesion and excellent electrolyte resistance, and even if the negative electrode active material layer breaks through the separator and contacts the positive electrode plate due to foreign matter or burrs, the negative electrode active material layer and the positive electrode current collector will not come into direct contact with each other, thereby ensuring that the secondary battery has high safety performance.

[0006] In any embodiment of the present application, the mass percentage content w1 of the resin is 1% to 5%, the mass percentage content w2 of the inorganic filler is 5% to 35%, and the mass percentage content w3 of the organic solvent is 60% to 94% relative to the total mass of the insulating slurry. By rationally adjusting the mass percentage contents of the resin, the inorganic filler, and the organic solvent, the blur width of the fusion region can be effectively reduced while significantly improving the application speed. The insulating coating thus obtained has high mechanical strength, high heat resistance, high insulating properties, high adhesion, and excellent electrolyte resistance at the same time, and the secondary battery using this insulating coating can have higher safety performance while having good electrochemical performance.

[0007] In any embodiment of the present application, w1 / w2 is 0.05 to 1. Optionally, w1 / w2 is 0.1 to 1. When w1 / w2 is within a suitable range, it is possible to effectively reduce the blur width of the fusion region while ensuring that the insulating coating simultaneously has high mechanical strength, high heat resistance, high insulating property, high adhesion and excellent electrolyte resistance.

[0008] In any embodiment of the present application, the insulating slurry has a viscosity of 1000 cps to 20000 cps at 25° C. Optionally, the insulating slurry has a viscosity of 3000 cps to 8000 cps at 25° C.

[0009] In any embodiment of the present application, the number average molecular weight of the polyfluorinated olefin resin is 600000 to 1500000. Optionally, the number average molecular weight of the polyfluorinated olefin resin is 1100000 to 1300000.

[0010] In any embodiment of the present application, the polyfluorinated olefin resin has a crystallinity of 30% to 60%. Optionally, the polyfluorinated olefin resin has a crystallinity of 40% to 50%.

[0011] In any embodiment of the present application, the melting point of the polyfluorinated olefin resin is 150° C. to 180° C. Optionally, the melting point of the polyfluorinated olefin resin is 155° C. to 175° C.

[0012] In any embodiment of the present application, the polyfluorinated olefin resin is selected from at least one of polyvinylidene fluoride resin, polyvinyl fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer resin, vinylidene fluoride-trifluoroethylene copolymer resin, vinylidene fluoride-trifluorochloroethylene copolymer resin, vinylidene fluoride-tetrafluoroethylene copolymer resin, and vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer resin.

[0013] In any embodiment of the present application, the two-dimensional inorganic material is in the form of layers, sheets or lamellae.

[0014] In any embodiment of the present application, the two-dimensional inorganic material is selected from at least one of layered silicate and two-dimensional molecular sieve. The layered silicate and the two-dimensional molecular sieve are in the form of a layer, a sheet or a thin plate, and can reduce the migration speed of the insulating slurry when it migrates to the positive electrode slurry application area, thereby reducing the blur width of the fusion area. The layered silicate and the two-dimensional molecular sieve also have strong adsorption ability, and can be bonded to the resin in the insulating slurry by van der Waals force, thereby further reducing the migration speed of the insulating slurry and the blur width of the fusion area.

[0015] In any embodiment of the present application, the layered silicate comprises at least one of mica powder, fluorophlogopite powder, talcum powder, hydrotalcite, and hydrotalcite-like compounds.

[0016] In any embodiment of the present application, the two-dimensional molecular sieve comprises at least one of MWW type, SAPO type, FER type, and PLS-n type molecular sieves.

[0017] In any embodiment of the present application, the two-dimensional inorganic material has a volume average particle size Dv50 of 0.5 μm to 10 μm. Optionally, the two-dimensional inorganic material has a volume average particle size Dv50 of 0.5 μm to 5 μm.

[0018] In any embodiment of the present application, the aspect ratio of the two-dimensional inorganic material is >= 50: 1. Optionally, the aspect ratio of the two-dimensional inorganic material is between 50: 1 and 100: 1.

[0019] In any embodiment of the present application, the organic solvent comprises at least one of N-methylpyrrolidone, triethyl phosphate, dimethylsulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide.

[0020] In any embodiment of the present application, the mass percentage content of the emulsifier in the insulating slurry is less than or equal to 1 / 1000000. Optionally, the mass percentage content of the emulsifier in the insulating slurry is 0%.

[0021] According to a second aspect of the present application, a method for producing an insulating slurry is provided, which includes the steps of: uniformly dispersing an organic solvent and an inorganic filler to obtain a first slurry (S100); and uniformly dispersing resin particles in the first slurry to obtain an insulating slurry (S200), in which the inorganic filler is selected from at least one of two-dimensional inorganic materials, and the resin particles are selected from at least one of polyfluorinated olefin resins produced by suspension polymerization.

[0022] In any embodiment of the present application, the mass percentage content of the resin particles is 1% to 5%, the mass percentage content of the inorganic filler is 5% to 35%, and the mass percentage content of the organic solvent is 60% to 94%, relative to the total mass of the insulating slurry.

[0023] In any embodiment of the present application, in S100, the dispersion linear velocity is 20 m / s to 100 m / s, and the dispersion time is 15 min to 120 min.

[0024] In any embodiment of the present application, in S200, the dispersion linear velocity is 20 m / s to 100 m / s, and the dispersion time is 120 min to 480 min.

[0025] In any embodiment of the present application, the method further comprises the step S300 of filtering the insulating slurry to obtain the insulating slurry. Optionally, the obtained insulating slurry is filtered using a 100-200 mesh screen.

[0026] In any embodiment of the present application, the resin particles are primary particles. The primary particles have a volume average particle diameter Dv50 of 20 μm to 150 μm. Optionally, the primary particles have a volume average particle diameter Dv50 of 50 μm to 100 μm.

[0027] According to a third aspect of the present application, there is provided a positive electrode plate including a positive electrode current collector, a positive electrode active material layer, and an insulating coating, in which the positive electrode active material layer is located on at least a part of a surface of the positive electrode current collector, and the insulating coating is located on the surface of the positive electrode current collector and contacts an edge of the positive electrode active material layer along a longitudinal direction of the positive electrode current collector, in which the insulating coating is a layer formed by drying an insulating slurry as described in the first aspect of the present application, or a layer formed after drying an insulating slurry produced by the method as described in the second aspect of the present application.

[0028] In any embodiment of the present application, the insulating coating has a thickness between 2 μm and 150 μm.

[0029] In any embodiment of the present application, the width of the insulating coating is between 0.1 mm and 15 mm.

[0030] According to a fourth aspect of the present application, there is provided a secondary battery including the positive electrode plate according to the third aspect of the present application.

[0031] According to a fifth aspect of the present application, there is provided a battery module including the secondary battery according to the fourth aspect of the present application.

[0032] According to a sixth aspect of the present application, there is provided a battery pack including at least one of the secondary battery according to the fourth aspect of the present application and the battery module according to the fifth aspect.

[0033] According to a seventh aspect of the present application, there is provided a power consumption device including at least one of the secondary battery according to the fourth aspect of the present application, the battery module according to the fifth aspect, and the battery pack according to the sixth aspect.

[0034] [Beneficial Effects] The insulating slurry of the present application can suppress the migration of the insulating slurry to the positive electrode slurry coating region by using a polyfluorinated olefin resin produced by a suspension polymerization method in combination with a two-dimensional inorganic material, and can also improve the coating speed while significantly reducing the blur width of the fusion region, thereby improving the safety performance of the secondary battery. The insulating slurry of the present application can also ensure that the secondary battery has a high energy density. The insulating coating produced by the insulating slurry of the present application can simultaneously have high mechanical strength, high heat resistance, high insulation, high adhesion and excellent electrolyte resistance, and even if the negative electrode active material layer breaks through the separator and contacts the positive electrode plate due to foreign matter or burrs, the negative electrode active material layer and the positive electrode current collector will not come into direct contact with each other, thereby ensuring that the secondary battery has high safety performance. The battery module, battery pack and power consumption device of the present application include the secondary battery of the present application, and therefore have at least the same advantages as the secondary battery. [Brief description of the drawings]

[0035] In order to more clearly describe the technical solutions of the embodiments of the present application, the following briefly introduces the drawings that need to be used in the embodiments of the present application. It is obvious that the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on the drawings without making creative efforts. In the drawings, the drawings are not necessarily drawn to actual scale. [Figure 1] FIG. 2 is a schematic diagram of one embodiment of a positive electrode plate of the present application. [Diagram 2] 1 is a schematic diagram of an embodiment of a secondary battery of the present application. [Diagram 3] FIG. 3 is an exploded view of the embodiment of the secondary battery of FIG. 2. [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application. [Diagram 5] 1 is a schematic diagram of one embodiment of a battery pack of the present application. [Figure 6] FIG. 6 is an exploded view of the embodiment of the battery pack shown in FIG. 5. [Figure 7] 1 is a schematic diagram of one embodiment of a power consuming device including a secondary battery of the present application used as a power source; [Figure 8] FIG. 1 is a comparison diagram of the results when the insulating slurries produced in Example 1 and Comparative Example 1 were applied at high speed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] Hereinafter, with reference to the drawings, embodiments specifically disclosing the insulating slurry and its manufacturing method, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0037] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the end values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. It is understood that if 1 and 2 are listed as minimum range values, and 3, 4 and 5 are listed as maximum range values, then the ranges 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" have already been listed in this specification, and "0-5" is merely a shorthand for combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure content of the present application.

[0039] Unless otherwise stated, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution, and such technical solution should be considered to be included in the disclosure content of the present application.

[0040] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0041] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.

[0042] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0043] In this application, the term "two-dimensional inorganic material" refers to an inorganic material that has a two-dimensional or nearly two-dimensional structure in its morphology, for example, the inorganic material has the morphology of a layer, sheet, or thin plate.

[0044] A secondary battery is also called a rechargeable battery or storage battery, and refers to a battery that can be used continuously after discharging by activating the active material in a charging manner. In general, a secondary battery includes an electrode assembly and an electrolyte, and the electrode assembly includes a positive electrode plate, a negative electrode plate, and a separator. The positive electrode plate includes a positive electrode collector and a positive electrode active material layer, the positive electrode active material layer is applied to the surface of the positive electrode collector, and the positive electrode active material layer includes a positive electrode active material. The negative electrode plate includes a negative electrode collector and a negative electrode active material layer, the negative electrode active material layer is applied to the surface of the negative electrode collector, and the negative electrode active material layer includes a negative electrode active material. During the charging and discharging process of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to be absorbed and released. The separator is provided between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short-circuiting between the positive and negative electrodes, and can also allow ions to pass through. The electrolyte serves to conduct active ions between the positive and negative plates.

[0045] Safety issues are an important factor that restrict the application and popularization of secondary batteries, among which internal short circuits affect the safety issues of secondary batteries and are the main cause of secondary battery failure. The internal short circuit forms of secondary batteries mainly include (1) a short circuit between the negative electrode collector and the positive electrode collector, (2) a short circuit between the negative electrode active material layer and the positive electrode active material layer, (3) a short circuit between the negative electrode active material layer and the positive electrode current collector, and (4) a short circuit between the positive electrode active material layer and the negative electrode current collector. Numerous studies have found that the short circuit between the negative electrode active material layer and the positive electrode current collector is the most dangerous, mainly because the negative electrode active material layer is a good conductor of electrons, so the impedance at the short circuit point is small, and after the short circuit, the voltage drops sharply and the temperature at the short circuit rises sharply, which may eventually cause combustion and even explosion.

[0046] In order to improve the safety performance of secondary batteries, a policy of applying an insulating treatment such as applying an insulating coating to the area adjacent to the positive active material layer on the surface of the positive electrode current collector is generally used. However, during the drying process of the positive electrode plate, the existing insulating slurry migrates to the area coated with the positive electrode slurry, and as a result, after drying is completed, a fusion area (commonly called a virtual edge, i.e., migration width of insulating coating to positive active material layer) is formed at the boundary between the positive active material layer and the insulating coating. The blur width of the fusion area is actually the distance that the insulating slurry migrates to the area coated with the positive electrode slurry, or the width of the area where the positive active material layer is covered with the insulating coating. The appearance of the fusion area leads to difficulty in positioning the CCD (Charge Coupled Device) visual inspection equipment during laser die cutting, inaccurate die cutting dimensions of the positive electrode plate, and even exposes the secondary battery to the risk of overhang, which poses serious safety risks to the secondary battery. In addition, the fusion region is actually a region formed by the insulating coating component and the positive electrode active material layer component being fused to each other, or a region formed by the positive electrode active material layer being coated with an insulating coating, so that the ion conduction performance of the fusion region is generally poor, which prevents / hinders the release and occlusion of some active ions, and the appearance of the fusion region also reduces the energy density of the secondary battery, and the wider the fusion region, the more significant the reduction in the energy density of the secondary battery. In addition, the faster the coating speed, the wider the fusion region, and further, for example, when high-speed coating with a coating speed of >30 m / min, the blur width of the fusion region may exceed 3 mm. This is mainly because the faster the coating speed, the higher the corresponding drying temperature, which improves the fluidity of the insulating slurry at high temperatures and reduces the surface tension, which makes it easier to move to the positive electrode slurry coating region.

[0047] With the application and widespread use of secondary batteries, the requirements for coating speed are becoming higher and higher, so there is a need for effective technical means for reducing the blur width of the fused region while increasing the coating speed.

[0048] Insulation Slurry According to a first aspect of the present application, an insulating slurry is provided, comprising a resin, an inorganic filler and an organic solvent, wherein the resin is selected from a polyfluorinated olefin resin produced by a suspension polymerization method, and the inorganic filler is selected from a two-dimensional inorganic material.

[0049] Polyfluorinated olefin resin has advantages such as excellent adhesion, electrolyte resistance, and electrochemical oxidation resistance, and is therefore currently widely used in positive electrode slurries and insulating slurries. However, the insulating slurry using polyfluorinated olefin resin will inevitably migrate to the positive electrode slurry coating area, and after drying, will form a wide fusion area at the boundary between the positive electrode active material layer and the insulating coating, and at the same time, the faster the coating speed, the wider the fusion area, which restricts the improvement of the coating speed. At present, engineers have not yet discovered the root cause of the formation of the fusion area, so in order to reduce the blur width of the fusion area and ensure the high safety performance of secondary batteries, existing technologies usually adopt the policy of reducing the coating speed.

[0050] The inventor of the present application, after much research, unexpectedly discovered that the reason why the existing insulating slurry is prone to form a wide fusion region is that the existing insulating slurry is a polyfluoroolefin resin produced by emulsion polymerization. An emulsion polymerization system usually contains four basic components, namely, a monomer, an emulsifier, an initiator, and water, among which, the function of the emulsifier in the emulsion polymerization system includes lowering the surface tension and dispersing the monomer into fine droplets, forming a protective layer on the surface of the droplets to prevent aggregation, and solubilizing. When producing polyfluoroolefin resin by emulsion polymerization, a fluorine-containing emulsifier is generally used, and the most commonly used fluorine-containing emulsifiers include pentadecafluorooctanoic acid (PFOA) and its alkali metal salts, perfluorobutanesulfonic acid, perfluorobutanesulfonic acid salts, perfluoropolyether, fluorine-containing polyether acids and their salts (e.g., perfluoropolyether carboxylic acid, perfluoropolyether ammonium carboxylate), etc. The emulsifier in the polyfluorinated olefin resin produced by emulsion polymerization is difficult to remove due to the polymerization process and other reasons, so the surface tension of the insulating slurry is low. In addition, since fluorine has the highest electronegativity, strong electron absorption, and high C—F bond energy, if the emulsifier used is a fluorine-containing emulsifier, its screen activity will be higher and the surface tension will be lower, so that the surface tension of the insulating slurry will be further reduced and significantly lower than that of the positive electrode slurry. Therefore, the insulating slurry of the polyfluorinated olefin resin produced by emulsion polymerization inevitably forms a wide fusion area, restricting the improvement of the coating speed.

[0051] The insulating slurry of the present application uses polyfluorinated olefin resin produced by suspension polymerization. A suspension polymerization system usually contains five basic components, namely, a monomer, a dispersant, an initiator, a chain transfer agent, and water, among which the main function of the dispersant is to maintain the stability of the polymerization system by adsorbing on the surface of the monomer liquid and to prevent the polymer particles from coalescing. When producing polyfluorinated olefin resin by suspension polymerization, a water-soluble dispersant, such as cellulose ether or polyvinyl alcohol, is generally used, and compared with emulsion polymerization, the amount of dispersant adsorbed on the polyfluorinated olefin resin particles produced by suspension polymerization is small, which makes it easy to remove and the resin purity is higher.

[0052] The insulating slurry of the present application does not contain an emulsifier or does not essentially contain an emulsifier, and its mass percentage content is below the lower detection limit, for example, ≦1 / 1000000. Therefore, compared with the insulating slurry obtained by using the polyfluorinated olefin resin produced by the suspension polymerization method of the present application and the existing insulating slurries, the surface tension is higher, so the difference in surface tension between the positive electrode slurry is smaller, and further, the insulating slurry of the present application can reduce the blur width of the fusion region.

[0053] In the technical proposal of the insulating slurry of the present application, a two-dimensional inorganic material is used as an inorganic filler. When the inorganic filler has a two-dimensional (or nearly two-dimensional) structure, the diffusion path of the liquid solution (i.e., the resin solution) to the positive electrode slurry application region becomes longer, and the diffusion resistance becomes larger. Therefore, using a two-dimensional inorganic material as an inorganic filler can reduce the migration speed of the insulating slurry and suppress the migration of the insulating slurry to the positive electrode slurry application region, thereby further reducing the blur width of the fusion region.

[0054] Therefore, in the technical solution of the insulating slurry of the present application, by using a polyfluorinated olefin resin produced by a suspension polymerization method in combination with a two-dimensional inorganic material, the migration of the insulating slurry to the positive electrode slurry coating area can be suppressed, and the width of the blurred area of ​​the fusion area can be significantly reduced while improving the coating speed, thereby improving the safety performance of the secondary battery. In the technical solution of the present application, when the coating speed is 60 m / min or more, the width of the blurred area of ​​the fusion area can be ≦0.5 mm, and even ≦0.2 mm, which is significantly better than the industry average level (when the coating speed is 30 m / min to 40 m / min, the width of the blurred area of ​​the fusion area is >2 mm). The technical solution of the insulating slurry of the present application can also ensure that the secondary battery has a high energy density. The insulating coating produced from the insulating slurry of the present application can simultaneously have high mechanical strength, high heat resistance, high insulation properties, high adhesion and excellent electrolyte resistance. Even if the negative electrode active material layer breaks through the separator and contacts the positive electrode plate due to foreign matter, burrs or the like, the negative electrode active material layer will not come into direct contact with the positive electrode current collector, thereby ensuring that the secondary battery has high safety performance.

[0055] In some embodiments, the mass percentage content w1 of the resin may be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any range of values ​​equal to or greater than 1%. Optionally, the mass percentage content w1 of the resin may be 1% to 5%, 1.5% to 5%, 2% to 5%, 2.5% to 5%, 3% to 5%, 3.5% to 5%, 4% to 5%, 1% to 4%, 1.5% to 4%, 2% to 4%, 2.5% to 4%, 3% to 4%, 3.5% to 4%, 1% to 3%, 1.5% to 3%, 2% to 3%, 2.5% to 3%, 1% to 2%, or 1.5% to 2%.

[0056] When the mass percentage content of the resin is high, the mechanical strength, heat resistance and insulation of the insulating coating are poor, and the direct contact between the negative electrode active material layer and the positive electrode current collector cannot be effectively prevented, and the risk of short circuit inside the secondary battery increases. At the same time, when the mass percentage content of the resin is high, the viscosity of the insulating slurry is generally high, making it difficult to apply, and when the mass percentage content of the resin is low, the adhesion and electrolyte resistance of the insulating coating are reduced, making it easy to fall off from the positive electrode current collector, and the safety performance during long-term use of the secondary battery cannot be ensured. Therefore, when the mass percentage content of the resin is within an appropriate range, the insulating coating has high mechanical strength, high heat resistance, high insulation, high adhesion and excellent electrolyte resistance at the same time, and even if the negative electrode active material layer breaks through the separator and contacts the positive electrode plate due to foreign matter or burrs, the negative electrode active material layer will not come into direct contact with the positive electrode current collector, thereby ensuring higher safety performance during long-term use of the secondary battery.

[0057] In some embodiments, the mass percentage content w2 of the inorganic filler may be 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 35%, or any range of values ​​above, relative to the total mass of the insulating slurry. Optionally, the mass percentage content w2 of the inorganic filler may be 5% to 35%, 10% to 35%, 15% to 35%, 20% to 35%, 25% to 35%, 30% to 35%, 5% to 32%, 10% to 32%, 15% to 32%, 20% to 32%, 25% to 32%, 5% to 30%, 10% to 30%, 15% to 30%, 20% to 30%, 25% to 30%, 5%-28%, 10%-28%, 15%-28%, 20%-28%, 25%-28%, 5%-26%, 10%-26%, 15%-26%, 20%-26%, 5%-24%, 10%-24%, 15%-24%, 20%-24%, 5%-22%, 10%-22%, 15%-22%, 5%-20%, 10%-20%, or 15%-20%.

[0058] When the mass percentage content of the inorganic filler is high, the adhesion and electrolyte resistance of the insulating coating are reduced, and the coating is easily detached from the positive electrode current collector, and the safety performance of the secondary battery during long-term use cannot be ensured, and when the mass percentage content of the inorganic filler is low, the mechanical strength, heat resistance and insulation of the insulating coating are poor, and the coating cannot effectively prevent direct contact between the negative electrode active material layer and the positive electrode current collector, and the risk of short circuit inside the secondary battery increases. Therefore, when the mass percentage content of the inorganic filler is within an appropriate range, the insulating coating simultaneously has high mechanical strength, high heat resistance, high insulation, high adhesion and excellent electrolyte resistance, and even if the negative electrode active material layer breaks through the separator and contacts the positive electrode plate due to foreign matter or burrs, the negative electrode active material layer and the positive electrode current collector will not come into direct contact with each other, thereby ensuring higher safety performance during long-term use of the secondary battery.

[0059] In some embodiments, the mass percentage content w3 of the organic solvent relative to the total mass of the insulating slurry may be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 94% or a range of any value greater than or equal to 60%. Alternatively, the mass percentage content w3 of the organic solvent is 60% to 94%, 65% to 94%, 70% to 94%, 75% to 94%, 80% to 94%, 85% to 94%, 90% to 94%, 60% to 90%, 65% to 90%, 70% to 90%, 75% to 90%, 80% to 90%, 85% to 90%, 60% to 85%, 65% to 85%, 70% to 85%, 75% to 85%, 80% to 85%, 60% to 80%, 65% to 80%, 70% to 80%, 75% to 80%, 60% to 75%, 65% to 75%, 70% to 75%, 60% to 70%, or 65% to 70%.

[0060] In some embodiments, the mass percentage content w1 of the resin is 1% to 5%, the mass percentage content w2 of the inorganic filler is 5% to 35%, and the mass percentage content w3 of the organic solvent is 60% to 94% relative to the total mass of the insulating slurry. By rationally adjusting the mass percentage contents of the resin, inorganic filler, and organic solvent, the blur width of the fusion region can be effectively reduced while significantly improving the coating speed. The insulating coating thus obtained has high mechanical strength, high heat resistance, high insulating properties, high adhesion, and excellent electrolyte resistance at the same time, and the secondary battery using this insulating coating can have higher safety performance while having good electrochemical performance.

[0061] When w1 / w2 is small, the mass percentage content of the inorganic filler is high, and the adhesion and electrolyte resistance of the insulating coating are poor, and when w1 / w2 is large, the mass percentage content of the inorganic filler is low, and the migration of the resin solution to the positive electrode slurry application area cannot be effectively suppressed, and the fusion area is more likely to spread. When w1 / w2 is within a suitable range, it is possible to ensure that the insulating coating has high mechanical strength, high heat resistance, high insulation, high adhesion and excellent electrolyte resistance at the same time while effectively reducing the blur width of the fusion area. In some embodiments, w1 / w2 is 0.05 to 1. Optionally, w1 / w2 is 0.1 to 1, 0.12 to 1, 0.15 to 1, or 0.18 to 1.

[0062] The viscosity of the insulating slurry mainly affects the coating performance of the insulating slurry, and when the viscosity is too high, the insulating slurry cannot be applied to the surface of the positive electrode current collector. At the same time, it is not preferable that the viscosity of the insulating slurry is too low, and in this case, the fluidity of the insulating slurry is high, and the fusion region is more likely to spread. In some embodiments, the viscosity of the insulating slurry at 25°C is 1000cps to 20000cps. For example, the insulating slurry may have a viscosity at 25°C of 1000 cps, 2000 cps, 3000 cps, 4000 cps, 5000 cps, 6000 cps, 7000 cps, 8000 cps, 9000 cps, 10000 cps, 11000 cps, 12000 cps, 13000 cps, 14000 cps, 15000 cps, 16000 cps, 17000 cps, 18000 cps, 19000 cps, 20000 cps, or a range consisting of any of the above numerical values. Alternatively, the insulating slurry may have a viscosity at 25° C. of 2000 cps to 20000 cps, 4000 cps to 20000 cps, 6000 cps to 20000 cps, 8000 cps to 20000 cps, 10000 cps to 20000 cps, 12000 cps to 20000 cps, 14000 cps to 20000 cps, 16000 cps to 20000 cps, 18000 cps to 20000 cps, 1000 cps to 15000 cps, 2000 cps to 15000 cps, 4000 cps to 15000 cps, 6000 cps to 15000 cps, 8000 cps to 15000 cps, 10000 cps to 15000cps, 12000cps~15000cps, 1000cps~10000cps, 2000cps~10000cps, 4000cps~10000cps, 6000cps~10000cps, 8000cps~10000cps, 1000cps~8000cps, 2000cps~8000cps, 3000cps~8000cps, 4000cps~8000cps, 5000cps~8000cps, 6000cps~8000cps, 1000cps~5000cps, 2000cps~5000cps, 3000cps~5000cps, or 4000cps~5000cps.

[0063] Considering that the insulating coating needs to have both excellent adhesion and excellent electrolyte resistance, the polyfluorinated olefin resin may have a medium molecular weight. In some embodiments, the number average molecular weight of the polyfluorinated olefin resin is 600,000 to 1,500,000. Optionally, the number average molecular weight of the polyfluorinated olefin resin is 1,100,000 to 1,300,000.

[0064] Considering that the insulating coating must have both excellent adhesion and excellent electrolyte resistance, and at the same time, considering the processing performance of the positive electrode plate, the polyfluorinated olefin resin may have a medium degree of crystallinity. If the crystallinity of the polyfluorinated olefin resin is low, its swelling in the electrolyte is high, the electrolyte resistance of the insulating coating is reduced, and the insulating coating is likely to fall off from the positive electrode current collector during long-term use of the secondary battery. If the crystallinity of the polyfluorinated olefin resin is high, the processing performance of the positive electrode plate manufactured therefrom is reduced, and the tape is likely to break during winding. In some embodiments, the crystallinity of the polyfluorinated olefin resin is 30% to 60%. Optionally, the crystallinity of the polyfluorinated olefin resin is 40% to 50%.

[0065] Considering that the insulating coating must have both excellent adhesion and excellent electrolyte resistance, and at the same time, considering the processing performance of the positive electrode plate, the polyfluorinated olefin resin may have a medium melting point. If the melting point of the polyfluorinated olefin resin is low, the degree of swelling in the electrolyte is high, the electrolyte resistance of the insulating coating is reduced, and the insulating coating is likely to fall off from the positive electrode current collector during long-term use of the secondary battery. If the melting point of the polyfluorinated olefin resin is high, the processing performance of the positive electrode plate manufactured therefrom is reduced, and the tape is likely to break during winding. In some embodiments, the melting point T m The melting point of the polyfluoroolefin resin is 150°C to 180°C. Optionally, the melting point of the polyfluoroolefin resin is 155°C to 175°C.

[0066] In some embodiments, the polyfluorinated olefin resin produced by the suspension polymerization process is selected from at least one of polyvinylidene fluoride (PVDF) resin, polyvinyl fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer (VDF-HFP) resin, vinylidene fluoride-trifluoroethylene copolymer resin, vinylidene fluoride-trifluorochloroethylene copolymer resin, vinylidene fluoride-tetrafluoroethylene copolymer resin, and vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer resin.

[0067] The polyfluorinated olefin resin produced by the suspension polymerization method may be purchased from Solvay or Kureha, and of course, the polyfluorinated olefin resin produced by the suspension polymerization method may be obtained by synthesis. Exemplary polyfluorinated olefin resins produced by the suspension polymerization method include at least one of commercially available Solef (registered trademark) 6008, Solef 6010, Solef 6012, Solef 6020, Solef 5120, Solef 5130, Solef 5140, Solef 9007, Solef 1015, Solef 75040, and Solef 75130.

[0068] In some embodiments, the two-dimensional inorganic material is in the form of layers, sheets, or lamellae.

[0069] In some embodiments, the two-dimensional inorganic material is selected from at least one of a layered silicate and a two-dimensional molecular sieve, and the layered silicate and the two-dimensional molecular sieve have a two-dimensional or nearly two-dimensional structure, such as a layer, a sheet, or a thin plate.

[0070] The crystal structure of layered silicates is composed of structural unit layers (or crystal layers) stacked in parallel to each other. The structural unit layers include two parts, sheet layers and interlayers. The sheet layers are usually composed of silicon-oxygen tetrahedral sheets and metal cations (e.g., Mg 2+ , Fe 2+ , Al3+ It is composed of silicon-oxygen octahedral sheets and aluminum-oxygen octahedral sheets in a 1:1 or 2:1 ratio. Between the sheet layers are intercalations, which may be empty or filled with water molecules, cations, anions, etc. Two-dimensional molecular sieves are aluminosilicates in a crystalline state having a spatial network structure in which silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra are alternately arranged.

[0071] The layered silicate and the two-dimensional molecular sieve used in the present application are in the form of a layer, a sheet, or a thin plate. When the insulating slurry migrates to the positive electrode slurry application region, the inorganic filler can increase the diffusion path and diffusion resistance of the liquid solution (i.e., the resin solution) to the positive electrode slurry application region, thereby reducing the migration speed of the insulating slurry and further reducing the blur width of the fusion region. The layered silicate and the two-dimensional molecular sieve also have strong adsorption ability, and can be bonded to the resin in the insulating slurry by van der Waals force, thereby further reducing the migration speed of the insulating slurry and the blur width of the fusion region.

[0072] Both layered silicate and two-dimensional molecular sieve have the advantages of good thermal stability and low cost, and at the same time, they have a sheet layer structure like graphite, and the van der Waals force of the interlayer structure is much smaller than the ionic force in the layer, so that interlayer friction can occur when extruded. Therefore, the insulating coating using the inorganic filler has better heat resistance and insulation, which can further improve the safety performance of the secondary battery. In addition, since layered silicate and two-dimensional molecular sieve also have good toughness, the positive electrode plate manufactured by them has good processing performance and is less likely to break when wound.

[0073] Optionally, the layered silicate comprises at least one of mica powder, fluorophlogopite powder, talcum powder, hydrotalcite, and hydrotalcite-like compounds.

[0074] Optionally, the two-dimensional molecular sieve includes at least one of MWW type, SAPO type, FER type, and PLS-n type molecular sieves. Illustratively, the two-dimensional molecular sieve includes at least one of MCM-22, MCM-49, MCM-56, SAPO-34, SAPO-18, and Al-PLS-3.

[0075] In some embodiments, when the insulating slurry contains at least one of mica powder and talcum powder, some of the transition metal impurities in the mica powder and talcum powder may be removed in advance by acid washing and water washing processes. These transition metal impurities may hinder the electrochemical performance of the secondary battery, for example, increasing the self-discharge of the secondary battery. In the present application, there is no particular limit to the number of times of acid washing and water washing, and it may be selected according to actual needs. For acid washing, it is preferable to use an aqueous solution of a weak acid, such as an aqueous solution of boric acid, and of course, a diluted solution of a strong acid, such as an aqueous solution of nitric acid, sulfuric acid, or hydrochloric acid with a mass fraction of about 1%, may be selected.

[0076] In some embodiments, the two-dimensional inorganic material has a volume average particle size Dv50 of 0.5 μm to 10 μm, for example, the volume average particle size Dv50 of the two-dimensional inorganic material can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range of any of the above values. Alternatively, the two-dimensional inorganic material has a volume average particle size Dv50 of 0.5 μm to 9 μm, 0.5 μm to 8 μm, 0.5 μm to 7 μm, 0.5 μm to 6 μm, 0.5 μm to 5 μm, 0.5 μm to 4 μm, 0.5 μm to 3 μm, 1 μm to 10 μm, 1 μm to 9 μm, 1 μm to 8 μm, 1 μm to 7 μm, 1 μm to 6 μm, 1 μm to 5 μm, 1 μm to 4 μm, or 1 μm to 3 μm.

[0077] The two-dimensional inorganic material is in the form of a layer, a sheet or a thin plate, so that the two-dimensional inorganic material generally has a high aspect ratio. When the aspect ratio of the two-dimensional inorganic material is small, its effect of reducing the migration speed of the insulating slurry is weak, and thus the blur width of the fusion region is slightly large. In some embodiments, the aspect ratio of the two-dimensional inorganic material may be ≧30:1, ≧40:1, ≧50:1, ≧60:1, ≧70:1, ≧80:1, ≧90:1, ≧100:1, ≧110:1, ≧120:1, ≧130:1, ≧140:1, ≧150:1. The larger the aspect ratio of the two-dimensional inorganic material, the more significant its effect of reducing the migration speed of the insulating slurry, but the higher the manufacturing cost of the two-dimensional inorganic material. In some embodiments, optionally, the aspect ratio of the two-dimensional inorganic material is 50:1 to 150:1, 50:1 to 140:1, 50:1 to 130:1, 50:1 to 120:1, 50:1 to 110:1, 50:1 to 100:1, 50:1 to 90:1, or 50:1 to 80:1.

[0078] In the present application, the type of the organic solvent is not particularly limited, and any compound known in the art that can dissolve the resin may be used. In some embodiments, the organic solvent includes at least one of N-methylpyrrolidone (NMP), triethyl phosphate, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0079] In some embodiments, the insulating slurry includes a resin, an inorganic filler, and an organic solvent, the resin being selected from a polyfluorinated olefin resin produced by a suspension polymerization method, and the inorganic filler being selected from a two-dimensional inorganic material. With respect to the total mass of the insulating slurry, the mass percentage content w1 of the resin is 1%-5%, the mass percentage content w2 of the inorganic filler is 5%-35%, and the mass percentage content w3 of the organic solvent is 60%-94%. The polyfluorinated olefin resin produced by the suspension polymerization method is selected from at least one of polyvinylidene fluoride resin, polyvinyl fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer resin, vinylidene fluoride-trifluoroethylene copolymer resin, vinylidene fluoride-trifluorochloroethylene copolymer resin, vinylidene fluoride-tetrafluoroethylene copolymer resin, and vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer resin. The two-dimensional inorganic material has a layered, sheet-like, or thin plate-like form. The aspect ratio of the two-dimensional inorganic material is ≧50:1. The material of the two-dimensional inorganic material is selected from at least one of layered silicate and two-dimensional molecular sieve.

[0080] In this application, the number average molecular weight of a resin has a meaning known in the art and may be measured using instruments and methods known in the art, for example, gel permeation chromatography (GPC), and may be tested using an Agilent 1290 Infinity II GPC system.

[0081] As used herein, the crystallinity of a resin has a meaning known in the art and may be measured using instruments and methods known in the art, for example, differential scanning calorimetry (DSC), such as a Mettler-Toledo DSC-3 differential scanning calorimeter.

[0082] In this application, the melting point of the resin has a meaning known in the art, and may be measured by using instruments and methods known in the art, for example, it may be measured with reference to GB / T 29611-2013 "Determination of glass transition temperature of raw rubber by differential scanning calorimetry (DSC)", and the test may be performed using a Mettler-Toledo DSC-3 type differential scanning calorimeter.

[0083] In this application, the viscosity of the insulating slurry has a meaning known in the art, and may be measured by using instruments and methods known in the art, for example, by referring to GB / T 2794-2013 "Measurement of Viscosity of Adhesives by Single Cylinder Rotational Viscometer Method".

[0084] In this application, the volume average particle size Dv50 of a material has the meaning known in the art, which means the particle size when the cumulative volume distribution rate reaches 50%, and may be measured using instruments and methods known in the art. For example, it may be simply measured using a laser particle size analyzer such as the Mastersizer 2000E type laser particle size analyzer of Malvern Panalytical Co., Ltd., UK, with reference to GB / T 19077-2016 particle size distribution laser diffraction method.

[0085] In this application, the aspect ratio of two-dimensional inorganic materials has a meaning known in the art, and may be measured by using instruments and methods known in the art, for example, by referring to JC / T 2063-2011 "Method for measuring aspect ratio of mica powder".

[0086] Manufacturing method of insulating slurry According to a second aspect of the present application, a method for producing an insulating slurry is provided, which includes the steps of: uniformly dispersing an organic solvent and an inorganic filler to obtain a first slurry (S100); and uniformly dispersing resin particles into the first slurry (S200) to obtain an insulating slurry, in which the inorganic filler is selected from at least one of two-dimensional inorganic materials, and the resin particles are selected from at least one of polyfluorinated olefin resins produced by suspension polymerization.

[0087] In some embodiments, the mass percentage content of the resin particles is 1% to 5%, the mass percentage content of the inorganic filler is 5% to 30%, and the mass percentage content of the organic solvent is 65% to 94%, relative to the total mass of the insulating slurry.

[0088] The resin particles are made of polyfluoroolefin resin produced by suspension polymerization, so that the particle size of the resin particles is generally large and difficult to aggregate. In some embodiments, the resin particles are in the form of primary particles. Optionally, the volume average particle size Dv50 of the primary particles is 20 μm to 150 μm. For example, the volume average particle size Dv50 of the primary particles may be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, or any range of values ​​above. Alternatively, the volume average particle size Dv50 of the primary particles is 30 μm to 150 μm, 50 μm to 150 μm, 70 μm to 150 μm, 90 μm to 150 μm, 20 μm to 120 μm, 30 μm to 120 μm, 50 μm to 120 μm, 70 μm to 120 μm, 90 μm to 120 μm, 20 μm to 100 μm, 30 μm to 100 μm, 50 μm to 100 μm, 70 μm to 100 μm, 20 μm to 80 μm, 30 μm to 80 μm, or 50 μm to 80 μm.

[0089] In some embodiments, in S100, the dispersion linear velocity is 20 m / s to 100 m / s, and the dispersion time is 15 min to 120 min.

[0090] In some embodiments, in S200, the dispersion linear velocity is 20 m / s to 100 m / s, and the dispersion time is 120 min to 480 min.

[0091] In some embodiments, the method further includes the step S300 of filtering the insulating slurry to obtain the insulating slurry. Optionally, the insulating slurry is filtered using a 100-200 mesh screen.

[0092] The insulating slurry manufacturing method of the second embodiment of the present application can manufacture the insulating slurry of the first embodiment of the present application. It should be noted that the relevant parameters of the insulating slurry manufactured by the insulating slurry manufacturing method of the second embodiment of the present application can refer to the insulating slurries according to the examples of the first embodiment of the present application.

[0093] positive electrode plate According to a third aspect of the present application, there is provided a positive electrode plate including a positive electrode current collector, a positive electrode active material layer, and an insulating coating, in which the positive electrode active material layer is located on at least a part of the surface of the positive electrode current collector, and the insulating coating is located on the surface of the positive electrode current collector and contacts an edge of the positive electrode active material layer along the longitudinal direction of the positive electrode current collector, and the insulating coating is a layer formed by drying an insulating slurry according to any one of the examples according to the first aspect of the present application, or a layer formed after drying an insulating slurry produced by a method according to any one of the examples according to the second aspect of the present application.

[0094] The positive electrode plate of the present application can reduce the probability of direct contact between the negative electrode active material layer and the positive electrode current collector, and ensure high safety performance of the secondary battery. The positive electrode plate of the present application also has good processing performance and is less likely to break during winding.

[0095] In some embodiments, the insulating coating is located on one or both sides of the positive electrode active material layer in the longitudinal direction. Optionally, the insulating coating is located on both sides of the positive electrode active material layer in the longitudinal direction. FIG. 1 is a schematic diagram of one embodiment of a positive electrode plate of the present application. As shown in FIG. 1, the positive electrode plate includes a positive electrode current collector 101, a positive electrode active material layer 102, and an insulating coating 103, and the insulating coating 103 is located on both sides of the positive electrode active material layer 102 in the longitudinal direction L, but the present application is not limited thereto.

[0096] In the present application, there is no particular limit to the thickness of the insulating coating, and it may be adjusted according to actual needs. In some embodiments, the thickness of the insulating coating is 2 μm to 150 μm.

[0097] In the present application, the width of the insulating coating is not particularly limited and may be adjusted according to actual needs. In some embodiments, the width of the insulating coating is 0.1 mm to 15 mm.

[0098] In some embodiments, the positive electrode current collector has two opposing surfaces in a thickness direction thereof, and the positive electrode active material layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0099] In some embodiments, the positive current collector has two opposing surfaces in a thickness direction thereof, and the insulating coating is disposed on either or both of the two opposing surfaces of the positive current collector.

[0100] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may adopt a positive electrode active material for a secondary battery known in the art. For example, the positive electrode active material may include at least one of a lithium transition metal oxide, a lithium-containing phosphate having an olivine structure, and a modified compound thereof. Examples of the lithium transition metal oxide may include at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and a modified compound thereof. Examples of the lithium-containing phosphate having an olivine structure may include at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and a modified compound thereof. The present application is not limited to these materials, and other conventionally known materials that can be used as a positive electrode active material for a secondary battery may be used. These positive electrode active materials may be used alone or in combination of two or more. In the present application, the modifying compound of each of the positive electrode active materials may be a doping modification of the positive electrode active material or a surface coating modification of the positive electrode active material.

[0101] In one embodiment, the positive electrode active material includes at least one of a lithium-containing phosphate having an olivine structure and a modified compound thereof.

[0102] In some embodiments, the positive electrode active material layer further optionally includes a positive electrode conductive agent. The present application is not particularly limited to the type of the positive electrode conductive agent, and for example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage content of the positive electrode conductive agent is ≦5% with respect to the total mass of the positive electrode active material layer.

[0103] In some embodiments, the positive electrode active material layer further optionally includes a positive electrode adhesive. The present application is not particularly limited to the type of the positive electrode adhesive, and for example, the positive electrode adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, the mass percentage content of the positive electrode adhesive is ≦5% with respect to the total mass of the positive electrode active material layer.

[0104] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. An example of the metal foil sheet may be aluminum foil. The composite current collector may include a polymer base layer and a metal material layer formed on at least one surface of the polymer base layer. For example, the metal material may be selected from at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0105] The positive electrode active material layer is generally obtained by applying a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is generally formed by dispersing a positive electrode active material, an optional conductive agent, an optional adhesive, and any other components in a solvent and uniformly stirring the mixture. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0106] The manufacturing method of the positive electrode plate of the present application is known in the art. In some embodiments, the positive electrode plate may be obtained by coating the positive electrode slurry and the insulating slurry described in any one of the embodiments according to the first aspect of the present application on a positive electrode current collector, drying, and cold pressing.

[0107] secondary battery A fourth aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, during charging and discharging of the secondary battery, active ions shuttle between the positive electrode plate and the negative electrode plate for occlusion and release, and the electrolyte serves to conduct the active ions between the positive electrode plate and the negative electrode plate.

[0108] [Positive electrode plate] The positive electrode plate used in the secondary battery of the present application is the positive electrode plate described in any one of the examples according to the third aspect of the embodiment of the present application.

[0109] [Negative electrode plate] In some embodiments, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces facing each other in a thickness direction thereof, and the negative electrode active material layer is disposed on one or both of the two facing surfaces of the negative electrode current collector.

[0110] The negative electrode active material may be a negative electrode active material for secondary batteries known in the art. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may include at least one of silicon elemental, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy material. The tin-based material may include at least one of tin elemental, tin oxide, and tin alloy material. The present application is not limited to these materials, and other conventionally known materials that can be used as secondary battery negative electrode active materials may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0111] In some embodiments, the negative electrode active material layer further optionally includes a negative electrode conductive agent. The present application is not particularly limited to the type of the negative electrode conductive agent, and for example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage content of the negative electrode conductive agent is ≦5% with respect to the total mass of the negative electrode active material layer.

[0112] In some embodiments, the negative electrode active material layer further optionally includes a negative electrode adhesive. The present application is not particularly limited to the type of the negative electrode adhesive, and for example, the negative electrode adhesive may include at least one of styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic acid-based resin (e.g., polyacrylic acid (PAA), polymethacrylic acid (PMAA), sodium polyacrylate (PAAS)), polyacrylamide (PAM), polyethylene alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage content of the negative electrode adhesive is ≦5% with respect to the total mass of the negative electrode active material layer.

[0113] In some embodiments, the negative electrode active material layer further optionally includes other additives. For example, the other additives may include a thickener, such as sodium carboxymethylcellulose (CMC-Na), a PTC thermistor material, etc. In some embodiments, the mass percentage content of the other additives is ≦2% based on the total mass of the negative electrode active material layer.

[0114] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. An example of the metal foil sheet may be copper foil. The composite current collector may include a polymer base layer and a metal material layer formed on at least one surface of the polymer base layer. For example, the metal material may be selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer base layer may be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0115] The negative electrode active material layer is generally obtained by applying a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is generally formed by dispersing a negative electrode active material, an optional conductive agent, an optional adhesive, and other optional auxiliary agents in a solvent and uniformly stirring the mixture. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0116] The negative electrode plate does not exclude any additional functional layers other than the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive undercoating (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode collector and the negative electrode active material layer and disposed on the surface of the negative electrode collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode active material layer.

[0117] [Electrolyte] The present application does not specifically limit the type of the electrolyte, and the electrolyte may be selected according to needs. For example, the electrolyte may be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte solution).

[0118] In some embodiments, the electrolyte employs an electrolyte solution, the electrolyte solution including an electrolyte salt and a solvent.

[0119] The type of the electrolyte salt is not specifically limited and can be selected according to actual needs. In some embodiments, for example, the electrolyte salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalato)phosphate (LiDFOP), and lithium tetrafluoro(oxalato)phosphate (LiTFOP).

[0120] The type of the solvent is not specifically limited and can be selected according to actual needs. In some embodiments, by way of example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).

[0121] In some embodiments, the electrolyte solution may further include optional additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, or an additive that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature performance of the battery, or an additive that improves the low temperature power performance of the battery.

[0122] [Separator] A separator is further included in secondary batteries using an electrolyte and some secondary batteries using a solid electrolyte. The separator is disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short circuit between the positive and negative electrodes and allows active ions to pass through. The present application is not particularly limited to the type of the separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected and used.

[0123] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film. When the separator is a multilayer composite film, the materials of each layer may be the same or different.

[0124] In some embodiments, the positive electrode plate, the separator and the negative electrode plate can be fabricated into an electrode assembly by a winding process or a stacking process.

[0125] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.

[0126] In some embodiments, the exterior body of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior body of the secondary battery may be a soft bag, such as a pouch-type soft bag. The material of the soft bag may be at least one of plastics, such as polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.

[0127] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. Figure 2 shows a secondary battery 5 with a rectangular structure as an example.

[0128] In some embodiments, as shown in FIG. 3, the exterior body may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening so as to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is permeated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or several, and may be adjusted according to needs.

[0129] The method for manufacturing the secondary battery of the present application is well known. In some embodiments, a secondary battery may be formed by assembling a positive electrode plate, a separator, a negative electrode plate, and an electrolyte. For example, a positive electrode plate, a separator, and a negative electrode plate may be formed into an electrode assembly by a winding process or a stacking process, and the electrode assembly may be placed in an outer casing, dried, and then an electrolyte may be injected, followed by vacuum packaging, standing, chemical formation, shaping, and other processes to obtain a secondary battery.

[0130] In some embodiments of the present application, the secondary battery according to the present application may be assembled into a battery module, and the number of secondary batteries included in the battery module may be multiple, and the specific number may be adjusted according to the application and capacity of the battery module.

[0131] Fig. 4 is a schematic diagram of an example battery module 4. As shown in Fig. 4, in the battery module 4, the multiple secondary batteries 5 may be arranged in order along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.

[0132] Optionally, the battery module 4 may further include an outer casing having an accommodation space, and the multiple secondary batteries 5 are accommodated in the accommodation space.

[0133] In some embodiments, the battery modules can be assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0134] 5 and 6 are schematic diagrams of an example battery pack 1. As shown in FIGS. 5 and 6, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is provided as a lid on the lower housing 3 and is used to form an enclosed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0135] power consumption equipment An embodiment of the present application further provides a power consuming device, the power consuming device including at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0136] The power consumption device can select a secondary battery, a battery module or a battery pack according to its usage demand.

[0137] 7 is a schematic diagram of an example power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, that may employ a battery pack or battery module to meet the high power and high energy density demands of the power consuming device.

[0138] As another example, the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. These power consuming devices are generally required to be thin, and may employ a secondary battery as a power source.

[0139] Working Example The following examples are provided to more specifically describe the contents disclosed in this application, and these examples are used for illustrative purposes only. This is because it is obvious to those skilled in the art that various modifications and changes can be made within the scope of the contents disclosed in this application. Unless otherwise stated, all parts, percentages, and ratios described in the following examples are based on mass, and all reagents used in the examples are commercially available or can be obtained by conventional synthesis and can be used directly without treatment, and the instruments used in the examples can be commercially available.

[0140] Of these, all of the polyfluorinated olefin resins produced by emulsion polymerization were purchased from Arkema, and all of the polyfluorinated olefin resins produced by suspension polymerization were purchased from Solvay.

[0141] Example 1 Insulating slurry manufacturing The talcum powder with a volume average particle diameter Dv50 of 2 μm and an aspect ratio of 100:1, which had been subjected to acid washing and water washing to remove impurities, was added to the organic solvent NMP and uniformly dispersed. The dispersion linear velocity was 22 m / s and the dispersion time was 60 min. The number average molecular weight was then measured to be 1,100,000, the crystallinity was 45%, and the melting point T mThe mixture is added with polyvinylidene fluoride (PVDF) resin Solef5130 at 172°C, the dispersion linear velocity is 20m / s, and the dispersion time is 240min. Finally, the mixture is filtered using a 150 mesh screen to obtain an insulating slurry. With respect to the total mass of the insulating slurry, the mass percentage content w1 of the resin is 3.8%, the mass percentage content w2 of the inorganic filler is 21.2%, and the mass percentage content w3 of the organic solvent is 75.0%.

[0142] Positive electrode plate manufacturing The positive electrode active material lithium iron phosphate, the conductive agent carbon black (Super P), and the adhesive polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:2 with an appropriate amount of NMP solvent and thoroughly stirred to form a uniform positive electrode slurry. The positive electrode slurry and the insulating slurry are uniformly applied to the surface of the positive electrode current collector aluminum foil at the same application speed according to the method shown in Figure 1, and then dried (dried until the NMP content in the positive electrode plate is <0.3%) and cold pressed to obtain a positive electrode plate. The application weight of the positive electrode slurry is 360 mg / 1540.25 mm 2 The coating width of the insulating slurry is 10 mm, and the coating speed is 60 m / min.

[0143] Negative electrode plate manufacturing The negative electrode active material graphite, the adhesive styrene butadiene rubber (SBR), the thickener sodium carboxymethylcellulose (CMC-Na), and the conductive agent carbon black (Super P) are mixed in a mass ratio of 96.2:1.8:1.2:0.8 with an appropriate amount of deionized water as a solvent and thoroughly stirred to form a uniform negative electrode slurry. The negative electrode slurry is uniformly applied to the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode plate is obtained.

[0144] Electrolyte production Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then thoroughly dried LiPF6 is dissolved in the organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L.

[0145] Separator manufacturing A porous polyethylene film is used as the separator.

[0146] Secondary battery manufacturing A positive electrode plate, a separator, and a negative electrode plate are stacked in that order and wound up to obtain an electrode assembly. The electrode assembly is then placed in an outer casing, dried, and then an electrolyte is injected. The secondary battery is obtained through processes such as vacuum packaging, leaving the battery to stand, chemical formation, and shaping.

[0147] Examples 2 to 21 and Comparative Examples 1 to 3 The manufacturing method of the secondary battery is similar to that of Example 1, and the difference is in the composition of the insulating slurry, and the specific parameter details are as shown in Table 1. Among them, the talcum powders or mica powders used in Examples 1 to 15, 19 to 21 and Comparative Example 3 were subjected to acid washing (hydrochloric acid aqueous solution with a mass fraction of 1%) and water washing treatment, while the talcum powder used in Example 16 was not subjected to acid washing or water washing treatment.

[0148] Comparative Example 4 The method for producing the secondary battery is similar to that of Example 1, except that the order in which the insulating slurry is added is different.

[0149] Number average molecular weight is 1,100,000, crystallinity is 45%, melting point T mPolyvinylidene fluoride (PVDF) resin Solef5130 having a temperature of 172°C is added to an organic solvent NMP and uniformly dispersed, the dispersion linear velocity is 22 m / s, and the dispersion time is 60 min. Then, in the dispersed state, talcum powder having a volume average particle diameter Dv50 of 2 μm and an aspect ratio of 100:1, which has been subjected to removal of impurities by acid washing and water washing, is added, the dispersion linear velocity is 20 m / s, and the dispersion time is 240 min. Finally, the mixture is filtered using a 150 mesh screen to obtain an insulating slurry. With respect to the total mass of the insulating slurry, the mass percentage content w1 of the resin is 3.8%, the mass percentage content w2 of the inorganic filler is 21.2%, and the mass percentage content w3 of the organic solvent is 75.0%.

[0150] Testing part (1) Viscosity test of insulating slurry The viscosity of the obtained insulating slurry is measured according to GB / T 2794-2013 "Measurement of Viscosity of Adhesives by Single Cylinder Rotational Viscometer Method". The test temperature is 25℃, and the test equipment is Brookfield DVS+ type rotational viscometer from Brookfield Corporation of the United States.

[0151] (2) Surface tension test of insulating slurry The surface tension of the obtained insulating slurry at 25° C. is measured using a DCAT9T type surface tension tester manufactured by Dataphysics, Germany.

[0152] (3) Analysis of high-speed application of insulating slurry The positive electrode plates corresponding to each Example and Comparative Example are measured for the blur width (i.e., maximum width) of the fusion region on the positive electrode plate by a CCD visual inspection device. The coating speeds of the positive electrode slurry and the insulating slurry in Comparative Example 1 and Comparative Example 3 are all 36 m / min, the coating speeds of the positive electrode slurry and the insulating slurry in Comparative Example 2 are all 45 m / min, and the coating speeds of the positive electrode slurry and the insulating slurry in Examples 1 to 21 are all 60 m / min.

[0153] (4) Electrolyte resistance test of insulating coating The positive electrodes of each embodiment and comparative example were immersed in the standard electrolyte at room temperature for 168 hours, and then the standard electrolyte was removed in a glove box. The insulating coating was repeatedly wiped off with a cotton swab until it fell off. The more times the cotton swab was wiped off, the better the electrolyte resistance of the insulating coating.

[0154] (5) Insulation coating adhesion test The secondary batteries manufactured in each Example and Comparative Example were charged at 60° C. to 3.65 V at a constant current of 1 C, then charged at a constant voltage of 3.65 V to a current of ≦0.05 mA, left to stand for 5 minutes, and then discharged at a constant current of 1 C to 2.50 V, which is one cycle charge / discharge process. After the secondary batteries were subjected to 500 cycle charge / discharge tests using the above method, the secondary batteries were disassembled to observe whether the insulating coating had fallen off from the positive electrode current collector.

[0155] (6) Secondary battery K value test The secondary batteries manufactured in each Example and Comparative Example are left at room temperature for 48 hours, and then the open-circuit voltage is tested and recorded as OCV1. The secondary batteries are left at room temperature for 48 hours, and then the open-circuit voltage is tested and recorded as OCV2. The K value of the secondary battery (mV / h) = (OCV1-OCV2) / 48.

[0156] (7) High-temperature cycle performance test of secondary batteries The secondary batteries prepared in each Example and Comparative Example were charged at 60° C. to 3.65 V at a constant current of 1 C, then charged at a constant voltage of 3.65 V to a current of ≦0.05 mA, and then discharged at a constant current of 1 C to 2.50 V after standing for 5 minutes, which is one cycle charge-discharge process. The secondary batteries were subjected to 500 cycle charge-discharge tests using the above method, and the capacity retention was measured.

[0157] Capacity retention (%) of the secondary battery after 500 cycles at 60° C.=discharge capacity at 500th cycle / discharge capacity at 1st cycle×100%.

[0158] (8) High-temperature storage performance test for secondary batteries The secondary batteries manufactured in each of the examples and comparative examples were charged to 3.65 V at room temperature with a constant current of 1 / 3 C, stored at 60°C for 60 days, and then held at room temperature for 5 hours. They were then discharged to 2.50 V at a constant current of 1 / 3 C, charged to 3.65 V at a constant current of 1 / 3 C, and further discharged to 2.50 V at a constant current of 1 / 3 C to obtain the discharge capacity of the secondary batteries after storage.

[0159] Capacity retention rate (%) after storing the secondary battery at 60° C. for 60 days=discharge capacity of secondary battery after storage / rated capacity of secondary battery×100%.

[0160] Table 2 shows the performance test results of Examples 1-21 and Comparative Examples 1-4.

[0161] FIG. 8 is a comparison diagram of the results when the insulating slurries prepared in Example 1 and Comparative Example 1 are applied at high speed. As shown in FIG. 8, the technical solution of the insulating slurry of the present application can effectively reduce the blur width of the fusion region. From the test results in Table 2, it can be seen that the blur width of the fusion region of the insulating slurry prepared in Example 1 at a coating speed of 60 m / min is only 0.4 mm, while the blur width of the fusion region of the insulating slurry prepared in Comparative Example 1 at a coating speed of 36 m / min reaches 2.2 mm. Therefore, in the present application, by combining the polyfluorinated olefin resin prepared by the suspension polymerization method with the two-dimensional inorganic material, the migration of the insulating slurry to the positive electrode slurry coating region can be suppressed, and the blur width of the fusion region can be significantly reduced while improving the coating speed.

[0162] In Comparative Example 2, the application speed can be improved to some extent by using a polyfluorinated olefin resin produced by a suspension polymerization method in combination with boehmite, which is a normal spherical or nearly spherical inorganic filler, and the blurred width of the fusion region can be reduced. However, the improvement effect is limited, and the blurred width of the fusion region at an application speed of 45 m / min of the insulating slurry reaches 1.0 mm, so it is difficult to use the insulating slurry produced in Comparative Example 2 at an application speed of 60 m / min or more. In Comparative Example 3, the application speed can be improved to some extent by using a polyfluorinated olefin resin produced by an emulsion polymerization method in combination with a two-dimensional inorganic material, and the blurred width of the fusion region can be reduced. However, the improvement effect is also limited, and the blurred width of the fusion region at an application speed of 36 m / min of the insulating slurry reaches 1.5 mm, so it is difficult to use the insulating slurry produced in Comparative Example 3 at an application speed of 60 m / min or more. In Comparative Example 4, when the insulating slurry is produced, the resin is added first, and then the inorganic filler is added, so that the inorganic filler cannot be uniformly dispersed.

[0163] From the test results in Table 2, it can be seen that by rationally adjusting the mass percentage contents of the resin, inorganic filler and organic solvent, the blur width of the fusion region of the positive electrode plate can be further reduced when w1 is 1%-5%, w2 is 5%-35%, and w3 is 60%-94%. Based on this, by further rationally adjusting the mass ratio of the resin and inorganic filler, when w1 / w2 is between 0.1 and 1, the adhesion and electrolyte resistance of the insulating coating can be improved.

[0164] The test results of Examples 1 and 19 to 21 also show that the higher the aspect ratio of the two-dimensional inorganic material, the more pronounced the effect of slowing down the migration speed of the slurry becomes, and the smaller the blur width of the positive electrode plate fusion region becomes.

[0165] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods constructed by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application.

[0166] [Table 1] JPEG0007651675000002.jpg209127JPEG0007651675000003.jpg210139JPEG0007651675000004.jpg210139JPEG0007651675000005.jpg21086

[0167] [Table 2] JPEG0007651675000007.jpg204137JPEG0007651675000008.jpg202140

Claims

1. An insulating slurry comprising a resin, an inorganic filler and an organic solvent, The resin is selected from polyfluorinated olefin resins produced by a suspension polymerization method, and the number average molecular weight of the polyfluorinated olefin resin is 900,000 to 1,500,000; The inorganic filler is selected from layered silicates and molecular sieves having a layer, sheet or plate shape; The insulating slurry has a viscosity of 1,000 cps to 20,000 cps at 25°C.

2. The insulating slurry according to claim 1, wherein the mass percentage content w1 of the resin is 1% to 5%, the mass percentage content w2 of the inorganic filler is 5% to 35%, and the mass percentage content w3 of the organic solvent is 60% to 94%, relative to the total mass of the insulating slurry.

3. The degree of crystallinity of the polyfluorinated olefin resin is 30% to 60%, and / or 3. The insulating slurry according to claim 1, wherein the melting point of the polyfluorinated olefin resin is 150°C to 180°C.

4. The insulating slurry according to claim 3, wherein the polyfluorinated olefin resin is selected from at least one of polyvinylidene fluoride resin, polyvinyl fluoride resin, polytetrafluoroethylene resin, vinylidene fluoride-hexafluoropropylene copolymer resin, vinylidene fluoride-trifluoroethylene copolymer resin, vinylidene fluoride-trifluorochloroethylene copolymer resin, vinylidene fluoride-tetrafluoroethylene copolymer resin, and vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer resin.

5. The layered silicate includes at least one of mica powder, fluorophlogopite powder, talcum powder, hydrotalcite, and hydrotalcite-like compounds; The insulating slurry according to any one of claims 1 to 4, wherein the molecular sieve having a layer, sheet or plate form includes at least one of MWW type, SAPO type, FER type and PLS-n type molecular sieves.

6. The layered silicate and the molecular sieve having a layered, sheet-like or plate-like form have a volume average particle diameter Dv50 of 0.5 μm to 10 μm, and / or 6. The insulating slurry according to claim 1, wherein the aspect ratio of the layered silicate and the molecular sieve having a layer, sheet or plate morphology is ≧50:

1.

7. The insulating slurry according to any one of claims 1 to 6, wherein the organic solvent includes at least one of N-methylpyrrolidone, triethyl phosphate, dimethylsulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.

8. The insulating slurry according to claim 1 , wherein the mass percentage content of the emulsifier in the insulating slurry is 1 / 1000000 or less.

9. A method for producing an insulating slurry, comprising the steps of: A step S100 of uniformly dispersing an organic solvent and an inorganic filler to obtain a first slurry; and a step S200 of adding resin particles to the first slurry in a dispersed state and dispersing the resin particles uniformly to obtain an insulating slurry. The method for producing an insulating slurry, wherein the inorganic filler is selected from layered silicate and a molecular sieve having a layer, sheet or plate shape, the resin particles are selected from a polyfluorinated olefin resin produced by a suspension polymerization method, the number average molecular weight of the polyfluorinated olefin resin is 900,000 to 1,500,000, and the viscosity of the insulating slurry at 25° C. is 1,000 cps to 20,000 cps.

10. 10. The method according to claim 9, wherein, relative to the total mass of the insulating slurry, the mass percentage content of the resin particles is 1% to 5%, the mass percentage content of the inorganic filler is 5% to 35%, and the mass percentage content of the organic solvent is 60% to 94%.

11. In S100, the dispersion linear velocity is 20 m / s to 100 m / s, and the dispersion time is 15 min to 120 min, and / or The method according to claim 9 or 10, wherein in S200, the dispersion linear velocity is 20 m / s to 100 m / s, and the dispersion time is 120 min to 480 min.

12. The method comprises: The method of any one of claims 9 to 11, further comprising the step S300 of filtering the resulting insulating slurry.

13. The method according to any one of claims 9 to 12, wherein the resin particles are primary particles, and the volume average particle diameter Dv50 of the primary particles is 20 µm to 150 µm.

14. A positive electrode plate, A positive electrode current collector; a positive electrode active material layer located on at least a portion of a surface of the positive electrode current collector; an insulating coating located on a surface of the positive electrode current collector and in contact with an edge of the positive electrode active material layer along a longitudinal direction of the positive electrode current collector; 9. A positive electrode plate, wherein the insulating coating is a layer formed after drying the insulating slurry according to claim 1.

15. the thickness of the insulating coating is between 2 μm and 150 μm; and / or The positive electrode plate of claim 14, wherein the insulating coating has a width of 0.1 mm to 15 mm.

16. A secondary battery comprising the positive electrode plate according to claim 14 or 15.

17. A battery module comprising the secondary battery according to claim 16.

18. A battery pack comprising the secondary battery according to claim 16 or the battery module according to claim 17.

19. A power consuming device comprising at least one of the secondary battery according to claim 16, the battery module according to claim 17, and the battery pack according to claim 18.

Citation Information

Patent Citations

  • Resin composition, filler-containing resin film for non-aqueous electrolyte secondary battery, and method for producing filler-containing resin film for non-aqueous electrolyte secondary battery

    CN104185651A

  • Electrochemical element separation membrane including low-resistance coating layer, and method for manufacturing same

    CN112106223A

  • Non-aqueous electrolyte secondary battery

    CN112864546A

  • Nonaqueous electrolyte secondary battery

    JP2020202039A

  • A positive electrode and an electrode assembly comprising the positive electrode

    KR1020200064752A